2019
DOI: 10.1002/aqc.3043
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of effective marine protected areas in Hawaiʻi

Abstract: Ancient Hawaiians developed sophisticated natural resource management systems that included various forms of spatial management. The state of Hawaiʻi established its first legislated marine protected area (MPA) in 1953, and today there exists a patchwork of spatial marine management strategies along a range of sizes, with varying levels of governance, enforcement, and effectiveness. Approximately 12% of waters within the 50 m depth contour and 5% of waters within state jurisdiction (≤3 nmi) have some form of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…Our results suggest that banning gear types could be effective for protecting fish biomass in this region. This is similar to a recent analysis of MPAs in Hawaii that showed both full and highly protected (typically limited to pole and line fishing) MPAs had greater fish than in areas of low or intermediate protection (Friedlander et al 2019). A global synthesis of the effectiveness of MPAs showed that the positive response to protection was primarily driven by targeted fish species (Sciberras et al 2013).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our results suggest that banning gear types could be effective for protecting fish biomass in this region. This is similar to a recent analysis of MPAs in Hawaii that showed both full and highly protected (typically limited to pole and line fishing) MPAs had greater fish than in areas of low or intermediate protection (Friedlander et al 2019). A global synthesis of the effectiveness of MPAs showed that the positive response to protection was primarily driven by targeted fish species (Sciberras et al 2013).…”
Section: Discussionsupporting
confidence: 88%
“…There is considerable evidence that supports that coral reef fishes will recover with reductions in fishing pressure (Campbell et al 2017). It is important to note, though, that for our study, there were very few sites representing no‐take areas, with some fully protected no‐take areas only recently established in West Hawaiʻi as late as 2016, where prior to 2016, there were only two full MPAs protecting only a small combined area of ~0.6 km ‐2 (Friedlander et al 2019). Long‐term observations of no‐take MPAs have shown that effects of MPA establishment can occur within 5 yr but can still take a decade or more to fully develop (Babcock et al 2010, Friedlander et al 2019).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…cornerstone of ecological studies used to identify biodiversity hotspots, infer the impact of natural or anthropogenic disturbance on communities, assess the effectiveness of management practices, and identify important habitats for species of conservation concern (e.g. Dorji et al, 2019;Friedlander et al, 2019;Ibarra & Martin, 2015;Rosenberg et al, 2017). For effective conservation decision-making to occur, biases associated with any given survey technique should be quantified and, where possible, corrected for.…”
mentioning
confidence: 99%